PELATIHAN DASAR DEWAN PENGAWAS SYARIAH (DPS) UNTUK LEMBAGA KEUANGAN SYARIAH - Waldelmi, Idel; Aquino, Afvan; Listihana, Wita Dwika (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
From the implementation of training carried out online / webinar Basic Training for Sharia Supervisory Board for Islamic financial institutions, results were obtained which stated that the PKM Basic Training for Sharia Supervisory Board for Islamic financial institutions that had been carried out, the following conclusions could be drawn: That the level of participation of the trainees who participated was very enthusiastic about joining, listening and discussing until the end of the implementation of this training. A strong sense and desire to know more, understand and a sense of desire (belief) to become part of the DPS members for Islamic financial institutions is highly desired by the training participants, this is also strongly corroborated by the distribution of free test and post test questionnaires, where the results of the implementation of training before and after training show results where the knowledge, understanding and belief of training participants after receiving basic material on the role of the sharia supervisory board for financial institutions are very interested in becoming part of the DPS members and looking forward to the next edition for more detailed training from DPS for Islamic financial institutions